Membangun Nilai Behavioral Intention melalui Tourist Experience : Studi Tentang Tourist Experience Dampaknya Terhadap Behavioral Intention di Floating Market Lembang - Ramdani Setiyariski (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2019)
Floating Market Lembang is a destination in Lembang, the boundary of West Bandung. Visitors visit in Floating Market Lembang always increasing in years. But that fact is not the same with the data which say tourist’s loyality haven’t maximum because majority of the tourist whose come to Floating Market lembang are new visitors. Decision of this research is to know influence of tourist experience to behavioral intention of Floating Market Lembang. The type of research are descriptive and verification. The survey method used is incidental sampling, which a sample size of 120 respondents. Data analysis technique using single regression techniques with coefficient determinant (R2) and partial (T) techniques. These results shows that there is a significant partial influence tourist experience to behavioral intention of Floating Market Lembang. The higher the ability of destination management in building positive experience on the tourists, so that it will increase positive image of the tourists in their visits. In this condition, directly or indirectly it will be able to build tourist’s willing in re-visiting to the destination. The correlation of the two variables can be simplisized in a sentence that in order to be able to build value of behavioral intention is how to be able to build tourist experience.